Pengaruh Tekanan Gas pada Proses Thermal Spray Aluminium (TSA) terhadap Keausan dan Morfologi Pada Baja ST 60 - Bram Ihza Pramudya; Sri Hastuti; Herru Santosa Budiono (Pusat Riset dan Inovasi Nasional, 2024)
The use of steel in industry continues to increase until now making it the material most often used in transportation equipment such as cars, ships and trains. Steel is used in the transportation construction industry, steel materials are often used for railway axle construction. Hardness values ​​were taken using the Vickers micro test, and wear using a taber abrasive tool. Based on this background, research will be carried out